Pengaruh Persepsi Korupsi, Keadilan Pajak, dan Sanksi Perpajakan Dalam Upaya Meningkatkan Kepatuhan Wajib Pajak - Whindi Ayu Mayrena; Dian Fahriani; Erlyna Tri Rohmiatun; Achmad Wicaksono (Forum Kerjasama Pendidikan Tinggi, 2026)
This study was conducted to examine the impact of three main variables perceptions of tax corruption, tax fairness, and tax penalties on the level of compliance among individual taxpayers in fulfilling their tax obligations. The researcher collected data by distributing questionnaires directly to taxpayers in the Sidoarjo Barat Pratama district, with a total sample of 99 respondents. This study employed a quantitative approach as the analytical method. The data analysis techniques applied included validity and reliability tests, multiple linear regression analysis, classical assumption tests, hypothesis testing, and the calculation of the coefficient of determination (R²), all processed using SPSS version 25 software. The research findings indicate that perceptions of tax corruption and tax sanctions have a significant effect on WPOP compliance, with significance values of 0.000 and 0.001, respectively. Conversely, the tax fairness variable did not demonstrate a significant effect on WPOP compliance, with a significance value of 0.798. The coefficient of determination (Adjusted R²) is 0.341, indicating that the variables of perceived corruption, tax fairness, and tax sanctions account for 34.1% of the variation in WPOP compliance. This study concludes that WPOP compliance is more influenced by external factors, particularly tax sanctions and perceptions of corruption, compared to perceptions of tax fairness